Nanoscale characterisation of MBE-grown GaMnN / (001) GaAs - Fay, Mike W.; Han, Y.; Novikov, Sergei V.; Edmonds, K.W.; Gallagher, B.L.; Campion, R.P.; Staddon, C.R.; Foxon, C.T.; Brown, Paul D. (Springer-Verlag, 2008)
The growth of cubic (Ga,Mn)N/(001)GaAs heterostructures by plasma assisted molecular beam epitaxy has been appraised as a function of Ga:N ratio, Mn concentration and growth temperature. The combined analytical techniques of EFTEM, EDX, CBED and dark field imaging have been used to appraise the Mn distributions within (Ga,Mn)N epilayers. Improved incorporation efficiency of Mn is associated with growth under N-rich conditions, but Mn incorporation may be enhanced under Ga-rich conditions at reduced growth temperatures. The surfactant behaviour of Mn during the growth of this spintronic system determines the resultant alloy composition.